Motion control of an aircraft electro-hydraulic servo actuator. (September 2019) - Fadel, M Z; Rabie, M G; Youssef, A M
Abstract: The use of the Fly-by-Wire (FBW) systems for flight control of aeronautical vehicles has increased steadily in the recent years. Such systems use electro-hydraulic servo-actuators to position the manoeuvring surfaces of airplanes or movable thrust vector controls of space vehicles. The marriage between electronics and hydraulic power systems has led to many powerful and precise control systems, saving much energy and money. This paper deals with the motion control of aircraft integrated electro-hydraulic servo-actuator (ISA) via development of a detailed nonlinear mathematical model and a computer simulation program using MATLAB/SIMULINK package. The ISA mainly consists of two separate active hydraulic power systems, used to supply the ISA with the required power. The studied ISA incorporates two electro-hydraulic servo-valves, a twin-symmetrical-hydraulic actuating cylinder, and a smart design of built in directional control valves with a feedback system. The output linear motion of the actuating cylinder of the ISA is presented and controlled by obtaining the transient response of the ISA. A classical PID controller is designed and tuned by Zeigler-Nichols method according to the Integral Square Error (ISE) criteria to minimize the difference between the obtained system output feedback and the desired set input by adjusting the system control parameters. The system stability and precision requirements are insured by applying the tuned PID controller.